Envosha Sdn Bhd / Muhammad Arafat Jelani - Jelani, Muhammad Arafat (Faculty Of Chemical Engineering, 2021)
19 weeks internship program at Envosha Sdn Bhd served as a platform for me to develop and increase myself worth. I am able to polish my technical and soft skills through the experience I gained during the training. I was trained to be independent especially when finding solutions out of the box for most of the task. From the practice given, I learned that creative and innovative thinking are important when finding solutions for any problems. The knowledge and skills I have received during the industrial training period has helped me to develop into a real working scenario specializing in safety and health industry. During my internship period, I have gained a lot of new knowledge. One of the most valuable skills I learned is the ability to speak with people in a professional setting where I understand that discussion with bosses and co-workers are different from discussion with lecturers or fellow students. Besides, I also learned on how to write a professional email and what the proper contents to be addressed are. During my internship period, there are times where I need to make my own decisions and do things on my own which was a great learning experience to make me more independent. On the other hand, I learned to accept constructive criticism well. All in all, Envosha Sdn Bhd is a good platform to gain knowledge and experience. By being an industrial trainee, I have been provided direct exposure to the work environment which provides valuable experience for a future career. Besides, I was also able to link and learn to apply the knowledge I gained in university and practice it in completing the tasks or projects assigned in work.